Preparation and study of simonkolleite and zinc oxide from aqueous precipitation of zinc chloride - Cousy, Simon (Univerzita Pardubice, 2019)
This work deals with the preparation of simonkolleite and zinc oxide from zinc chloride. The main motivation for this work was the preparation of nanoparticles using no surfactant, inexpensive setup and chemicals. A wet precipitation method was chosen for the synthesis, using potassium hydroxide as a precipitation agent for the zinc chloride salt. The precipitation mechanism was studied, as well as the influence of the synthesis parameters on the morphology and nature of the product. Additionally, the addition of butanol to the aqueous suspension was studied, as a stabilizer for simonkolleite suspension. Simonkolleite was synthesized in the shape of nano-platelets, whereas zinc oxide exhibited aggregates of nano and microspheres. Both simonkolleite and zinc oxide had limited dispersion stability in water suspension and showed some sedimentation. Finally, three different potential applications were studied for the products: as an anti-corrosive agent, as a photocatalyst, and as a filler for polymer reinforcement.
Příprava a studium simonkolleitu a oxidu zinečnatého z vodného srážení chloridu zinečnatého
Keywords: oxid zinečnatý; simonkolleit; mokré srážení; kompozit; chlorid zinečnatý; zinc oxide; simonkolleite; wet precipitation; composite; zinc chloride